99.5k views
4 votes
PLZZZZZZZZ HLPPPPPPPPPPPPP MEEEEEEEEEEEEE

PLZZZZZZZZ HLPPPPPPPPPPPPP MEEEEEEEEEEEEE-example-1
User Glazed
by
5.4k points

1 Answer

4 votes

Answer:

(x1,y1)=(−2,2)

(x2,y2)=(0,−2)

Use the slope formula:

m= y2−y1 /x2−x1

= −2−2 /0−−2

= −4 /2

=−2

Answer:

m=−2 This is the slope

So,the slope intercept form for 2 points is y-y1=m(x-x1) m=slope

y-y1=m(x=x1)

y-2=-2(x-(-2) ( - and - is +) So,the final equation is:

y-2=-2(x+2)

I hope this help you :)

User Ase
by
6.2k points